2022
DOI: 10.2106/jbjs.rvw.22.00124
|View full text |Cite
|
Sign up to set email alerts
|

Graft Options for Hip Labral Reconstruction

Abstract: Arthroscopic hip labral reconstruction is a complex procedure which is growing in use as indications, techniques, and surgical expertise advance.Graft selection is an important component of labral reconstruction based on relative advantages and disadvantages of available types of autografts and allografts.The ideal graft should mimic the native acetabular labrum form and function while also being affordable, readily available, and associated with low morbidity.High rates of patient satisfaction and positive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
(146 reference statements)
0
4
0
Order By: Relevance
“…Labral reconstruction emphasizes recapitulation of labrum structure and function in order to reestablish joint health. 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Labral reconstruction emphasizes recapitulation of labrum structure and function in order to reestablish joint health. 5 …”
Section: Introductionmentioning
confidence: 99%
“… 10 , 16 , 17 , 18 , 19 , 20 , 21 Meniscus allografts have been recently implemented for open labral reconstruction based on their similarities in size, shape, and geometry; tissue composition and architecture; synthetic and metabolic profiles; and material properties when compared to acetabular labrum tissue. 5 , 22 , 23 , 24 , 25 , 26 , 27 In an effort to avoid the morbidity associated with open hip surgery and replicate the advantages noted for outpatient surgery with use of tendon allografts, we have developed an arthroscopic technique for hip labral reconstruction using fresh meniscal allograft.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple labral reconstruction techniques have been described [5], with allograft being the preferred choice for reconstruction among high-volume surgeons [16]. However, although numerous techniques using a ligamentum teres autograft [30], iliotibial band autograft [22], gracilis autograft [17], quadriceps tendon autograft [20], capsular autograft [8], indirect head of the rectus femoris autograft [28], semitendinosus allograft [24], peroneus brevis tendon allograft [19], and meniscus allograft [7] have been reported, no single graft type has been demonstrated to be superior in acetabular labral reconstruction [1].…”
Section: Introductionmentioning
confidence: 99%
“…One promising allograft source for labral reconstruction is the human meniscus because of its similarities to the labrum in size, shape, tissue architecture, and material properties relative to tendon tissue [3,6]. Proof-ofconcept small case series have shown that meniscal allografts can be used clinically for acetabular labral reconstruction in humans, with no adverse events in the short term [3,6]. Further studies examining the histologic and biomechanical benefits of this reconstruction technique are therefore warranted.…”
mentioning
confidence: 99%